2023
DOI: 10.1590/1519-6984.242676
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi activity in the rhizosphere of tree seedlings subjected to residual herbicides

Abstract: Trees occurring on the margins of agricultural areas can mitigate damage from residual herbicides. Rhizospheric microbial activity associated with trees is one of the main remedial capacity indicators. The objective of this study was to evaluate the rhizospheric microbiological activity in tree species subjected to the herbicides atrazine and sulfentrazone via the rhizosphere. The experiment was designed in four blocks and a 6 × 3 factorial scheme. The first factor consisted of six tree species from Brazil and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Recent research has shown that microorganisms play a role in the degradation of these persistent pollutants (Kaur et al 2022 ). Bacterial and fungal species that have the ability to biodegrade MPs were identified (Dos Santos et al 2023 ). These are, for example, Rhodococcus sp.…”
Section: Soil Pollutionmentioning
confidence: 99%
“…Recent research has shown that microorganisms play a role in the degradation of these persistent pollutants (Kaur et al 2022 ). Bacterial and fungal species that have the ability to biodegrade MPs were identified (Dos Santos et al 2023 ). These are, for example, Rhodococcus sp.…”
Section: Soil Pollutionmentioning
confidence: 99%